Transformasi Digital Pelaksanaan Pembelajaran Tematik Di Sekolah Selama Masa Pandemi - Vinca Desti Mardiana; Dian Hidayati (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2022)
Abstract: The emerging COVID-19 pandemic has had a major impact on the course of life, including the world of education. The impact of the COVID-19 pandemic has changed the shift in the world of education, which was originally done face-to-face, and has shifted its direction to online learning. This shift in the concept of learning requires a transformation by utilizing digital technology. The purpose of this study was to determine the form and process of digital transformation carried out in carrying out thematic learning activities during distance learning at the basic education level. The subjects of this study were 3 people consisting of the principal and 2 teachers with the criteria of teaching thematic learning at SD Al Azhar 38 Bantul. The data collection technique used interviews. The validity of the data used triangulation of sources and techniques. Data analysis includes data reduction, data presentation, and conclusions. The results showed that SD Al Azhar 38 Bantul carried out a digital transformation in thematic learning during the covid-19 pandemic by utilizing platforms such as pinto, zoom, google meet, and WhatsApp. Meanwhile, the digital transformation process carried out by SD Al Azhar Bantul itself goes through several stages, namely digital transformation planning; organizing digital transformation; implementation of digital transformation; and control over digital transformation. Keywords: Pandemic, Digital Transformation, Thematic Learning